Military Power: A Strategic View - Nitze, Paul (Tufts Archival Research Center, 2005)
Volume 5, Issue 1. Winter During a visit to the Fletcher School, Paul H. Nitze addressed a Politics seminar on the problem of "Military Power and Political Influence." What follows are Mr. Nitze's remarks and his subsequent discussion with the students in that seminar. He emphasizes, like Karl von Clausewitz, that students should take "a strategic view" of international security which attempts to incorporate all the elements of international relations into a comprehensive problem-solving matrix.